Study on the Potential of Azolla pinnata as Larvicidal of Aedes aegypti - Nurul Nadiah Rozhan (2018)
In Malaysia, Dengue is a serious problem as Dengue irrespectively attacks all age group which vulnerable to children and young adult. In order to avoid the spreading diseases such as Dengue fever, there is need of vector control, but mostly relies on chemical insecticides. The continuous usage of chemical insecticide cause environmental hazard and increase the resistance of mosquitoes. Besides, there is need of emphasizing of biological control such as in present study use the plant derived insecticide. For this purpose, a study was undergo to analyse the larvicide effect of fresh Azolla pinnata plant to mosquito species, Aedes aegypti. Fresh Azolla pinnata has been acclimatized weighed in different weight for being placed in plastic container containing 500 ml distilled water together with third late instar and early fourth instar of Aedes aegypti larvae for 24 hour and 48 hours treatment. The larval mortality of Aedes aegypti were observed separately in l,5,l0,20,40,60,80,1O0 and 120 g of Azolla pinnata after 24 hour and 48 hour of treatment. Based on result, no mortality was observed in the control group, but lowest mortality recorded at l and 5 g at 24 hour treatment. The highest mortality was recorded at weight of 100 g at 48 hour treatment which is 70%. The behaviour of larvae of Aedes aegypti was observed. For 24 hour treatment, LC50 is 185.544 g/mL, LC9@ is 455.906 g/mL and LC99 is 948.802 g/mL. For 48 hour treatment, LC50 is 46.560 g/mL, LC90 is 160.280 g/mL, and LC99 is 439.106 g/mL. Diagnostic dose for 24 hour treatment is 1897.604 g/mL while for 48 hour treatment is 878.212 g/mL. Results showed that Azolla pinnata plant has potential to be a good larvicidal against dengue vector, Aedes aegypti. Further investigations are strongly recommended for identiﬁcation of bioactive compound of Azolla pinnata in order to be good larvicide in the future.